Applications and usability of interactive TV : 5th Iberoamerican Conference, jAUTI 2016, La Habana, Cuba, November 21-25, 2016, Revised selected papers /: 5th Iberoamerican Conference, jAUTI 2016, La Habana, Cuba, November 21-25, 2016, Revised selected papers. (2017) - Unknown
No abstract available